Konsep Manajemen Syariah Dalam Membangun Pola Fikir Generasi Milenial Terhadap Bank Muamalat - Nurwani Nasution; Chuzaimah Batubara (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
In the life of the increasingly advanced millennial generation and intense competition, all parties are required to organize all work systematically with the aim that what has been planned at the beginning can be achieved properly.  Likewise, a company is required to be able to keep up with the times.  All of that can be done well if the company implements good management.  Likewise with sharia-based companies.  The development of the Islamic banking system in Indonesia is carried out within the framework of a dual banking system or dual banking system within the framework of the Indonesian Banking Architecture (API), to present a more complete alternative banking service to the Indonesian people.  Management in Islam is the activity of ordering, organizing and thinking that contains the values of faith and monotheism, structuring a good organization and system in accordance with the Qur'an and sunnah of the Prophet.  The millennial generation or generation Y is widely known as the generation born between 1980 and 2000. The millennial generation is goal-oriented and has a high level of self-confidence and independence.  The millennial generation, which was born along with the development of technology, often has more knowledge about the digital world than its predecessor generations.  Rapidly advancing technological knowledge launched the millennial generation into an era where everything can be accessed easily from various places and by anyone.  This type of research includes field research.  Field research is used by digging up data sourced from locations or field research.  This study uses qualitative methods, qualitative methods are research based on natural object conditions, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out in triangulation (combined), data analysis is qualitative in nature, and the results of the research are more  Emphasize meaning over generalizations.